Stacja kolejowa jako miejsce graniczne na drodze do nowoczesności. Sól ziemi. Powieść o cierpliwym piechurze Józefa Wittlina - Piotrowski, Grzegorz (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2022)
In the present article, I utilize the first part of Józef Wittlin’s novel Sól ziemi. Powieść o cierpliwym piechurze [Salt of the earth. A novel about a persistent walker] to present changes in the perception of railway in the wake of World War I. On the example of Piotr Niewiadomski – the main character of the discussed work – I analyze how owing to this mean of transport millions of people were moved into a new dimension of reality, in which humanity has been reduced to the role of replaceable parts of immense machineries – railway and war.
Keywords: regional studies; region; Silesia; Poland; Czech Republic; Germany; regional journal; historical journal